Teaching English in the Colombian Rural: Normalistas Superiores Challenges and Experiences - Ortiz García, William Ricardo; Contreras Pinilla , Adriana Marcela (Universidad Pedagógica y Tecnológica de Colombia, 2023)
This qualitative study focuses on the challenges and experiences faced by normalistas in-service educators who teach English as a Foreign Language (EFL) in rural contexts in Colombia without the training to do so. Data were analyzed using grounded theory, through instruments such as interviews, real-life episodes, and a focus group. The participants were two normalistas educators who have taught English in rural areas for years, and the study was conducted in remote rural communities in Colombia with limited resources and connectivity. The results evidenced the teaching English practices outlook in rural communities, the adaption to an experimental learning and teaching method as part of the normalistas’ limitations in terms of English knowledge and instruments to teach the foreign language and, finally, the impact on rural learners as a result of normalistas’ performances in English classes.